Smart Construction Implementation in the Malaysian Construction Industry - Ayob, Yazira; Janipha, Nurul Afida Isnaini; Norazwan Booi, Izza Izzati (Built Environment Journal, 2025)
Smart construction involves the entire process of advancing digitisation, connectivity, visualisation, automation, and intelligence. Malaysia has recently started implementing smart construction, particularly in line with Industrial Revolution (IR) 4.0. Therefore, this research aims to investigate the implementation of smart construction in the Malaysian construction industry. Two (2) objectives were outlined: to identify the components of smart construction and to determine the benefits of smart construction in the Malaysian construction industry. An extensive literature review was done to obtain general information related to the components of smart construction and its benefits at large. A 254 questionnaire surveys were distributed to the G7 contractors in Johor via an online platform to learn in-depth about the components and benefits of smart construction in the Malaysian context. 31% of responses were obtained and analysed using Statistical Package for Social Sciences (SPSS) software. Findings revealed two (2) main components of smart construction: digital technologies and manufacturing, and five (5) core benefits have been identified. Thus, the emergence of smart construction will lead to better construction site management, proper construction monitoring, enhanced resource and asset management, and improved workplace safety. This research acts as a continuous source of information for the ongoing research undertaken by the author on the need to establish smart construction concepts in the Malaysian construction industry.